Pengaruh Harga, Kualitas Pelayanan dan Destinasi Terhadap Keputusan Menggunakan Jasa Dhani Tour and Travel Sukoharjo - Alfian Rasyid Rafiansyah; Sri Isfantin Puji Lestari; Agus Triatmono (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the effect of price, service quality and destination on the decision to use the services of Dhani Tour and Travel Sukoharjo. This study covers the field of marketing management. The population in this study were consumers of Dhani Tour and Travel Sukoharjo during 2023, totaling 136 consumers. The sample in this study was 100 consumers. The basis for taking this sample was by random sampling according to the number of samples determined, so that each employee has an equal opportunity to be selected as a sample (Sugiyono, 2010: 64). Data collection used in this study was using documentation and personal questionnaires. Keywords : the influence of price, service quality and destination on the decision to use services